2020
DOI: 10.1111/jsr.12988
|View full text |Cite
|
Sign up to set email alerts
|

Associations of objectively measured sleep characteristics and incident hypertension among police officers: The role of obesity

Abstract: Sleep is essential to maintaining good physical and mental health. The literature on sleep physiology shows that non-rapid and rapid eye movement alternate cyclically during sleep and that each stage is associated with distinct brain activities and physiological changes, such as blood pressure and heart rate fluctuation (Colten & Altevogt, 2006). Previous studies have suggested that sleep disorders (such as difficulty initiating and maintaining sleep)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(52 reference statements)
0
10
0
1
Order By: Relevance
“…[ 39 ] A study with a 7-year follow-up reported that each 10-minute increase in sleep latency was associated with an 89% increase in hypertension risk (95% CI: 1.12–3.20). [ 31 ] Another study also found that a longer sleep latency in women with hypertension. [ 40 ]…”
Section: Discussionmentioning
confidence: 98%
“…[ 39 ] A study with a 7-year follow-up reported that each 10-minute increase in sleep latency was associated with an 89% increase in hypertension risk (95% CI: 1.12–3.20). [ 31 ] Another study also found that a longer sleep latency in women with hypertension. [ 40 ]…”
Section: Discussionmentioning
confidence: 98%
“…Blood pressure measurements for all participants were taken during a single visit. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured at 2-min intervals, and the average of the three measurements was calculated consecutively ( 27 ). Anthropometric variables, including height (in centimeters), weight (in kilograms), waist circumference (in centimeters), and hip circumference (in centimeters) measurements of all participants were measured using standardized techniques and equipment by two trained interviewers; body mass index (BMI) was calculated by dividing weight in kilograms by height in meters squared (kg/m2) ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…A fisiopatologia da insônia pode ser explicada por alguns autores pelo "modelo hiperexcitação", caracterizada por um estado instável, com hipoativação do núcleo pré-óptico ventrolateral (VLPO), o que impede a ativação eficiente do sono pela via GABAérgica, e hiperativação do sistema ativador reticular ascendente (SARA), responsável pela excitação da via orexinérgica/hipocretinérgica. Apesar da coerente descrição, essa teoria é baseada em evidências empíricas e defendida por muitos autores (Young, Da;2020).…”
Section: Introductionunclassified